Simultaneous Analysis of Multiple Staphylococcal Enterotoxin Genes by an Oligonucleotide Microarray Assay - Sergeev, Nikolay (American Society for Microbiology, 2004)
Staphylococcal enterotoxins (SEs) are a family of 17 major serological types of heat-stable enterotoxins that are one of the leading causes of gastroenteritis resulting from consumption of contaminated food. SEs are considered potential bioweapons. Many Staphylococcus aureus isolates contain multiple SEs. Because of the large number of SEs, serological typing and PCR typing are laborious and time-consuming. Furthermore, serological typing may not always be practical because of antigenic similarities among enterotoxins. We report on a microarray-based one-tube assay for the simultaneous detection and identification (genetic typing) of multiple enterotoxin (ent) genes. The proposed typing method is based on PCR amplification of the target region of the ent genes with degenerate primers, followed by characterization of the PCR products by microchip hybridization with oligonucleotide probes specific for each ent gene. We verified the performance of this method by using several other techniques, including PCR amplification with gene-specific primers, followed by gel electrophoresis or microarray hybridization, and sequencing of the enterotoxin genes. The assay was evaluated by analysis of previously characterized staphylococcal isolates containing 16 ent genes. The microarray assay revealed that some of these isolates contained additional previously undetected ent genes. The use of degenerate primers allows the simultaneous amplification and identification of as many as nine different ent genes in one S. aureus strain. The results of this study demonstrate the usefulness of the oligonucleotide microarray assay for the analysis of multitoxigenic strains, which are common among S. aureus strains, and for the analysis of microbial pathogens in general.